Penerapan Sholat 40 Dalam Rangka Meningkatkan Kedisiplinan Ibadah Jamaah Surau Jambak Kalawi - Mirantika, Pebri; Putri, Sherlya; Rahmadani, Corry; Putri, Firli Amanda; Ramadan, Doli Pardi; Antoni, Jefri; Wassalam, Sabri; Arifin, Puadil; Alim, Nur; Saputra, Edriagus; Afnita, Nora (Institut Agama Islam Sumatera Barat, 2024)
The 40th prayer is a prayer that is performed in congregation within 40 days. This prayer is mostly performed by people who are getting older, both men and women. They usually live in the surau where the 40 prayers are held, the 40 prayers are usually led by a lord, in this case the implementation of the 40 prayers can increase the congregation's discipline in prayer services so that their prayers can be disciplined according to the specified time. Korong Sungai Community From another perspective, durian is a good tradition in order to get used to praying in congregation. This tradition of praying 40 days in congregation takes place every year, in 2024 the Islamic Institute will hold a real work lecture at Korang Sungai Durian and participate in the running of the tradition of 40 prayers, starting from 1 August 2024 to 9 September 2024. This research The aim is to find out the impact of implementing 40 prayers in order to improve the worship discipline of the Jambak Kalawi surau congregation. The main focus of this research is to see how the congregation participates in the 40 prayers that have been carried out.